Familial concern and adolescent simultaneous polysubstance use on American Indian reservations - Smith, Joey K., author; Conner, Bradley T., advisor; Swaim, Randall C., committee member; Riggs, Nathaniel R., committee member (Colorado State University. Libraries, 2019)
American Indian (AI) adolescents are at increased risk for substance misuse and related problems. AI adolescents initiate consumption earlier compared to non-American Indian (non-AI) adolescents, and are three times more likely to be diagnosed with a substance use disorder than non-AI adolescents. AI families may be more tolerant of substance misuse than non-AI families, and are likely to employ parenting styles which emphasize modeling and the importance of extended family. There is considerable literature on AI substance misuse, but to date no studies have examined simultaneous polysubstance misuse (SPM) within this population. SPM is the ingestion of two or more substances within the same period of time, so that the effects of the substances overlap. The synergistic effects of SPM are related to increasingly problematic outcomes in adolescents, such as increased substance misuse. Based on previous research, 3 hypotheses were offered: (1) that four proposed subscales, Substance Misuse Concern, Substance Misuse Deterrence, Substance Misuse Discussion, and Parental Monitoring, would comprise the latent construct Familial Oversight; (2) that Familial Oversight would significantly negatively predict increased likelihood of SPM endorsement; and (3) that this relation would be significantly moderated by participant's self-identified race, such that, for AI individuals the relation between Familial Oversight and SPM would be stronger than for non-AI individuals. Data were collected from middle and high school students (n = 4661) attending schools on or near AI reservations. Structural equation modeling was utilized to test the hypothesized model. Results indicated that modeling Familial Oversight as a unidimensional latent variable resulted in excellent model fit, x2(2) =20.23, p < .05; CFI = 0.994; SRMR = .064; RMSEA = .044 (90% C.I. [.128 - .063]); however, the factor loadings supported a two-factor model. Following modifications, a two-factor model of parenting was created with Parental Monitoring as a separate latent construct and the three remaining factors indicating the latent variable Familial Attitudes on the Misuse of Substances (FAMS); the modified model demonstrated excellent fit, x2(8) =32.87, p < .05; CFI = 0.997; RMSEA = .026 (90% C.I. [.017 - .035]). The two-factor model indicated SPM was negatively associated with Parental Monitoring (b = -0.131, S.E. = 0.033, b = -4.04, p < .001) but not significantly related to FAMS (b = -0.044, S.E. = 0.025, b = -1.79, p = .07). Finally, a multigroup SEM was conducted to test invariance, which demonstrated strong fit, x2(32) = 91.42, p < .05; CFI = 0.980; RMSEA = .028 (90% C.I. [.022 - .035]); however, self-identified racial status did not moderate the relations (p > .05). Though the proposed construct was not successfully indicated, Parental Monitoring demonstrated that parental awareness was important in significantly reducing the risk of SPM. Given AI adolescents' increased risk of negative outcomes, the known relation of AI substance misuse to familial influences, and Parental Monitoring's ability to reduce risk, it is important to understand how these factors are related to SPM.
Keywords: American Indian; addiction; polysubstance misuse